2014
DOI: 10.1021/ie501048a
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Catalytic Performance of Zr,Al-Pillared Clays in the Synthesis of Propylene Glycol Methyl Ether

Abstract: Series of Al-, Ga-, and Zr,Al-pillared clays (Al-MM, Ga-MM, and Zr,Al-MM) were prepared through the intercalation of Al-, Ga-, and Zr-polyoxocations into three layered aluminosilicates with various textural properties and chemical compositions. Zr,Al-phases with the structure of bayerite–boehmite were also synthesized using Al and Zr oligomeric solutions, prepared from aluminum chloride and zirconium oxychloride, respectively, as metal sources, with Zr/Al ratios of 0–0.143. All materials were characterized by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…Keeping the data of the IR study of the ZIF‐8 catalyst in mind and reaction mechanisms in the presence of oxygen‐containing materials,, , , , we can suggest that the mechanism of the reaction between MeOH and PO in the presence of ZIF‐8 systems consists of the following steps:…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Keeping the data of the IR study of the ZIF‐8 catalyst in mind and reaction mechanisms in the presence of oxygen‐containing materials,, , , , we can suggest that the mechanism of the reaction between MeOH and PO in the presence of ZIF‐8 systems consists of the following steps:…”
Section: Resultsmentioning
confidence: 99%
“…Different catalytic systems relevant to this process are reported in the literature. These systems include alkaline catalysts (hydroxides of alkali and alkaline‐earth metals),, amino‐functionalized SiO 2 , immobilized ionic liquid 1,1,3,3‐tetramethylguanidinium lactate on bentonite and SBA‐15 (IL/Support),, M x O y (M – Cu, Fe, Zn, Sn, and Ni), MgO,, metal phosphate molecular sieves, Al‐, Ga‐, Zr‐, and Zr, Al‐pillared clays (PILCs), natural and synthetic layered double hydroxides (LDHs) …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that a high strength of strong basic sites can lead to a strong stabilization of methoxide and propylene-like species which formed as intermediates on the surface of the solid and, in this way, hinder the process of reaction. 8 The element ratio of the catalyst and the reaction conditions were also studied. In Table 2, we investigated the element ratio of the catalyst and found that SiO 2 @Ce 0.33 Mg 2 A 1 -LDO(P123) has the best catalytic activity.…”
Section: Catalytic Synthesis Of Propylene Glycol Methyl Ethermentioning
confidence: 99%
“…There are numerous oligomeric cations that could be used as pillars, as well as Al, Zr, Ti, Cr, Fe, Ce and others [ 1 , 3 , 4 ]. These cations could be used individually [ 2 , 5 , 6 , 7 , 8 ] or mixed [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. In addition, there is an enormous amount of work dealing with the use of Al-pillared clays as supports of metal nanoparticles (Pd and Pt, for example) for several catalytic applications [ 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%